Simultaneous quantitation of urine aldosterone and tetrahydroaldosterone in healthy Chinese subjects using a validated LC–MS/MS method - Cheng, Jenny Yeuk Ki; Lo, Clara Wai Shan; Chan, Alan Shek Lun; Luk, Yue Kin; Tsui, Teresa Kam Chi; Ho, Chung Shun (Biomedical chromatography, 2023)
Aldosterone (ALD) is excreted in urine mainly as glucuronide conjugates of ALD and tetrahydroaldosterone. Measuring these urinary metabolites might be an alternative screening test to plasma ALD for primary aldosteronism. We report a validated LC–MS/MS method to measure both analytes simultaneously. Urine samples underwent enzymatic hydrolysis to release the analytes from their glucuronide conjugates followed by organic solvent extraction and LC–MS/MS. The analytical performance of this method was evaluated. The within‐batch and between‐batch coefficients of variation for urine ALD and urine THA were all ≤5.2 and ≤3.7%. The lower limit of quantification was 0.5 nmol/L, and the linearity was up to at least 2770 nmol/L for both analytes. No significant matrix interference and carryover were observed. Both analytes in urine were stable for at least 48 h at 10°C and at least 18 months at −80°C. Local reference intervals were established from 126 healthy normotensive Chinese subjects (53% women, age: 20–65 years). Reference intervals for urine ALD and tetrahydroaldosterone were 2–38 and 9–139 nmol/day, respectively. This validated method can be applied to screening and diagnosing primary aldosteronism.